Beslutsunderlag för energianpassade gallringar i Västerbotten - Lindkvist, Nils (2011)
The demand for renewable energy is increasing in Sweden. This consequently increases the pressure for and willingness to pay for forest fuels. One method to extract forest fuel from suitable commercial thinnings is the "long top method” (LT-method). With this method saw logs and non-delimbed tops are recovered, i.e. no pulpwood is recovered. Branches from delimbed sawlogs are not recovered and only long top (with branches and needles still attached) is hauled the landing site. To optimize income from the LT-method knowledge about the share of recovery of respectively saw logs and fuel wood at different stand conditions and top diameters are needed.